The secret spiral of Swamp Kid : a graphic novel - Scroggs, Kirk (DC Zoom, 2019)
Middle schooler Russell Weinwright, who is half kid and half swamp creature, depicts his daily life in his spiral notebook full of doodles and journal entries detailing what it's like being different and how to be comfortable in his own skin.